An EAACI "European Survey on Adverse Systemic Reactions in Allergen Immunotherapy (EASSI)": the methodology. Issue 1 (21st July 2014) - Calderón, Moises A; Rodríguez del Río, Pablo; Vidal, Carmen; Just, Jocelyne; Pfaar, Oliver; Linneberg, Allan; Demoly, Pascal
Abstract: At present, there is no European report on clinically relevant systemic reactions due to the regular use of allergen immunotherapy (AIT), administered either subcutaneously or sublingually (SCIT and SLIT, respectively) outside clinical trials. Using an electronic survey and a "harmonised terminology" according to MedDRA, we aimed to prospectively collect systemic adverse reactions due to AIT from real life clinical settings. Under the framework of the EAACI, a team of European specialists in AIT, pharmacovigilance, epidemiology and drugs regulation set up a web‐based prospective pilot survey to be conducted in three European countries (France, Germany and Spain). A designated "national coordinator" was responsible for following ethics requirements relative to each country and to select at least 30 doctors per country. Patients were recruited the same day they received their first dose of either SCIT or SLIT. Patient inclusion criteria were: adults and children, with IgE mediated pollen, house dust mite, Alternaria, and/or animal dander respiratory allergies who will initiate AIT. A list of 31 symptoms terms were extracted from the MedDRA (Medical Dictionary for Regulatory Activities) dictionary to harmonize the reporting of all adverse systemic reactions in this survey. The SurveyMonkey® online instrument was used by participant doctors to submit information directly to a blinded central database. Three questionnaires were generated: i) the Doctor Questionnaire, ii) the Patient Questionnaire and iii) the Adverse Reaction Questionnaire. A handbook and a mistake report form were given to each doctor. In this paper, we describe the methodology followed.